1987
DOI: 10.1128/aac.31.5.774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ciprofloxacin on eucaryotic pyrimidine nucleotide biosynthesis and cell growth

Abstract: Several of the new 4-quinolones significantly increase the incorporation of [3HJthymidine into the DNA of mitogen-stimulated human lymphocytes. This study suggests that ciprofloxacin inhibits de novo pyrimidine biosynthesis, thereby resulting in a compensatory increase in the uptake of pyrimidine precursors through salvage pathways, and that additional effects may affect eucaryotic cell growth. Incorporation of deoxyuridine, uridine, and orotic acid as well as thymidine was increased in the presence of ciprofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Ciprofloxacin at 20 jig/ml was shown to inhibit the progression of mitogen-stimulated lymphocytes through the S and G2/M stages of the cell cycle and to decrease the secretion of immunoglobulins G and M in pokeweed mitogen-stimulated B cells (21). The (6,20,21 (30) and the unscheduled DNA synthesis (UDS) test, the latter of which is run with quinolones incubated in rat hepatocyte cell cultures and also with rat hepatocytes removed from animals dosed with the test quinolone and analyzed directly (38). A number of quinolones are inhibitory in some of these in vitro genotoxicity tests, although positive in vivo tests are rare (Table 1).…”
Section: Reported Effects Of Quinolones On Eucaryotic Topoisomerases mentioning
confidence: 99%
“…Ciprofloxacin at 20 jig/ml was shown to inhibit the progression of mitogen-stimulated lymphocytes through the S and G2/M stages of the cell cycle and to decrease the secretion of immunoglobulins G and M in pokeweed mitogen-stimulated B cells (21). The (6,20,21 (30) and the unscheduled DNA synthesis (UDS) test, the latter of which is run with quinolones incubated in rat hepatocyte cell cultures and also with rat hepatocytes removed from animals dosed with the test quinolone and analyzed directly (38). A number of quinolones are inhibitory in some of these in vitro genotoxicity tests, although positive in vivo tests are rare (Table 1).…”
Section: Reported Effects Of Quinolones On Eucaryotic Topoisomerases mentioning
confidence: 99%
“…This irreversible formation of DNA strand breakage induces a sequence of events that leads ultimately to cell death. Recently published data (18,19,24,27,34) …”
mentioning
confidence: 99%
“…This irreversible formation of DNA strand breakage induces a sequence of events that leads ultimately to cell death. Recently published data (18,19,24,27,34) show that quinolones may affect some eucaryotic enzymes, especially those involved in DNA synthesis. However, as pointed out by Gootz et al (22), there are relatively few reports on this topic, and none assaying the four pro-and eucaryotic topoisomerases together.…”
mentioning
confidence: 99%
“…The new 4-quinolones bind to DNA (9) and significantly increase the incorporation of [3H]thymidine into the DNA of mitogenstimulated human lymphocytes (1)(2)(3), indicating a stimulation of DNA synthesis in vitro. It has also been suggested that the quinolones may affect de novo pyrimidine biosynthesis and at high concentrations inhibit cell growth in vitro (2) No significant differences were found in the mean yield of any aberration type or of the total number of aberrations between before and after 1 week of treatment with either ciprofloxacin or ofloxacin (Table 1). There were no differences in cytogenetic effects between the two treatment groups for any of the individual parameters or for the total number of aberrations.…”
mentioning
confidence: 99%